Estrutura filogenética de habitat em gradiente topográfico na floresta atlântica - Botacim, Luciana Aparecida (2023)
Setting the connection between the evolutionary history of species and topographic variation will allow a better understanding of the mechanisms of organization of biological communities along topographic gradients. However, little is known about this relationship between the evolutionary history of species and topographic gradients in the tropics. In this study, we evaluated how the evolutionary history of species contributes to the organization of local communities along topographic gradients. The study was conducted in a tropical forest fragment in southeastern Brazil. Species composition (115 in total) was obtained from surveying 100 plots (10m x 10m) along a topographic gradient. We grouped the plots into four habitats along the gradient: Valley, South slope, North slope, and Ridge. Phylogenetic distance indices were calculated for the different topographic elevations, the metrics of sesMPD and sesMNTD, which define the degree of relatedness between species (weighted and unweighted by abundances) and the phylogenetic diversity defined by the metric sesPD. We found greater phylogenetic diversity at the Ridge. The standardized phylogenetic metrics indicated significant values for phylogenetic patterns considering only the presence and absence of species. Contrary to expectations, Valley presented a phylogenetic clustering, i.e., that is, a community composed mainly of phylogenetically closer species. Ridge showed overdispersion, i.e. that is, a community with a predominance of phylogenetically more distant species. We did not find significant values indicating phylogenetic patterns in the structure of the community when weighing the weight of abundance. This suggests that it is more likely that environmental filtering is acting more strongly to organize the understory of this tropical community. Our findings demonstrate that the evolutionary history of species plays an important role in structuring tropical communities along topographic gradients.